MORPHOMETRIC VARIABLES AND INDIVIDUAL VOLUME OF MACROCYCLOPS ALBIDUS AND CYCLOPS VICINUS FEMALES (COPEPODA, CYCLOPOIDA) FROM HAZAR LAKE (ELAZIG-TURKEY) - Tellioglu, A. (Shiraz Univ, 2007)
Macrocyclops albidus and Cyclops vicinus are the two important copepods living in Hazar Lake. For this study, 50 females for each species were collected. Samples were taken between December 1999 and March 2000. Length (PL), width (PW), and height (PH) of prosome and length (UL) and width (UW) of urosome were measured in each female and subsequently, the following ratios PL/PW, PL/PH, PW/PH, PL/UL and UL/UW were determined. Volumes for M. albidus and C. vicinus females were estimated following the morphometric method Regression tests were conducted for both species between volume and prosome length or width. Regression lines were compared through covariance analysis. PL/UL was the best ratio for separating one species from the other. Average individual volume and standard error estimated for M. albidus and C. vicinus were 0.0063 (+/- 0.001) mm(3) and 0.0049 (+/- 0.001) mm(3) respectively. Differences between both copepods morphometric variable and rate values were observed. Measured size and volume values increased in March and June compared with December. According to R 2 values of regression lines, prosome width and prosome length were good volume predictors on different dates for M. albidus and C. vicinus. Differences in slopes and mean variances found between regression lines demonstrated variability according to different months.
Keywords: Cyclops vicinus; females; Hazar Lake; Macrocyclops albidus; morphometric variables; volume